Induction of cytochrome P450 via upregulation of CAR and PXR: a potential mechanism for altered florfenicol metabolism by macranthoidin B in vivo - Li, Si-cong; Wang, Bin; Zhang, Min; Yin, Qin; Yang, Zi-yi; Li, Xu-ting; Liang, Ge (Frontiers in Pharmacology, 2024)
Macranthoidin B (MB) is a primary active component of Flos Lonicerae. In Chinese veterinary clinics, Flos Lonicerae is frequently used in combination with florfenicol to prevent and treat infections in livestock and poultry. However, potential interactions between Flos Lonicerae and florfenicol remain unclear. This study investigates the impact of MB co-administration on the pharmacokinetics of florfenicol in vivo alongside various underlying mechanisms, particularly the influence of MB on the mRNA and protein expression of CYP1A2, CYP2C11, CYP3A1, UGT1A1, and P-gp, as well as CYP1A2 and CYP2C11 activities. We also explore MB’s effect on the expression and subcellular localization of nuclear receptors CAR, PXR, and RXRα in hepatocytes. The results indicate that MB significantly reduces the AUC(0-∞) and MRT(0-∞) of florfenicol. MB also markedly upregulates the mRNA and protein expression of hepatic CYP1A2 and CYP2C11, along with their catalytic activities. Substantial upregulation of CAR and PXR proteins occurs in the hepatocyte nucleus, along with significant nuclear colocalization of the transcriptionally active CAR/RXRα and PXR/RXRα heterodimers, indicating MB-induced nuclear translocation of both CAR and PXR. These findings suggest that MB-induced alterations in florfenicol pharmacokinetics, particularly its accelerated elimination, may be due to increased expression and activities of CYP1A2 and CYP2C11, with CAR and PXR potentially involved in these regulatory effects. Further investigation is yet needed to fully elucidate the clinical implications of these interactions concerning the efficacy of florfenicol in veterinary medicine.